Four-Wheel Patrol Efforts by the Turjawali Unit of the Samapta Unit to Prevent Crimes of Attacks in the Legal Area of ​​the Nganjuk Police - Hutapea, Ricky Johannes (Police Studies Review, 2024)
This study discusses the effectiveness of four-wheeled patrols by the Turjawali Unit of the Samapta Division of the Nganjuk Police in preventing mobbing crimes. A qualitative methodology and field research were employed, with theories of routine activity, management, SWOT, and Hotspot Policing used as analytical tools. The findings indicate that the four-wheeled patrols have not been effective in preventing mobbing due to poor management and imprecise targeting, as well as internal and external challenges. It is recommended that the patrol methods be refined as a preventive measure against public order disturbances, particularly mobbing in the jurisdiction.